The molecular target and mode of action of the acylurea insecticide, diflubenzuron - Kumari, Meera (Kansas State University, 2015)
In this study, I have used dsRNA-mediated down-regulation of transcripts/proteins of several potential targets in the model beetle, Tribolium castaneum to identify a molecular target of the “chitin inhibitor”, diflubenzuron (DFB). The elytron of the red flour beetle, T. castaneum, was chosen as the model tissue for studying the mode of action of DFB and its molecular target(s). We have standardized the protocol for topical administration of DFB on precisely aged prepupae to achieve the desired level of mortality (90-95%) on day 5 of the pharate adult stage. Exposure of prepupae to DFB at 1000 ppm results in a near complete loss of chitin in the newly forming adult procuticle of the elytron and the body wall. Global analysis of transcripts by RNA Seq was carried out to look for differential expression of several critical genes of cuticle assembly in these insects compared to mock-treated controls. Interestingly, genes directly involved in the biosynthetic pathway of chitin were not among those affected by DFB. However, immunolocalization studies have shown that several proteins of chitin metabolism including chitin synthase A, which is involved in the synthesis of cuticular chitin, are present in near normal amounts but are mislocalized in DFB-treated insects. Assays for chitin synthase using elytral extracts have indicated that the enzyme preparations from DFB-treated insects are catalytically inactive. By using RNA interference and competition studies with fluorescently-tagged glibenclamide (a sulfonylurea compound) or DFB, we have identified a long-sought molecular receptor of DFB as an ABCC class transporter. DFB-treatment and RNAi of a specific ABCC-type transporter gene lead to identical phenotypes including loss of chitin, loss of laminar architecture of the cuticle, and mislocalization of CHS from its normal plasma membrane location to intracellular locations presumably by affecting vesicular transport. Further, using an in vitro chitin synthesizing system consisting of microsomes prepared from elytral tissue, which exhibits all of the hallmarks of cuticular chitin-synthesizing epidermal cells including sensitivity to DFB, further insights into the mechanistic details of how this class of insecticides inhibits chitin synthesis have been obtained.
Keywords: Chitin inhibitor; Diflubenzuron; Molecular target; ABC transporter; Mode of action